Implementation of Group Counseling using Cognitive Restructuring Techniques to Enhance Career Maturity of Dayah Inshafudin High School Students in Banda Aceh - Sulma Mafirja; Siti Zahra Bulantika (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2020)
The purpose of this study was to determine the implementation of Group Counseling by using cognitive restructuring techniques to enhance the Career Maturity of students at SMA Dayah Inshafudin Banda Aceh. The method used in this study was quasi-experimental with a one-group pretest-posttest design. The subjects in the study were eight students who had low levels of self maturity. Data collection techniques in this study used the Self-Scale or CMI (Career Maturity Inventory). The results showed that the career maturity of students could be improved by using group counseling using cognitive restructuring techniques, as evidenced by the results of data analysis using Wilcoxon different tests, from the pretest and posttest results obtained z-output <z-table (z = -2,527; p = .012). The conclusion in this study is that student career maturity can be improved by group counseling services using cognitive restructuring techniques..